The Role of Atopy in COPD and Asthma - Karakioulaki, Meropi; Papakonstantinou, Eleni; Goulas, Antonios; Stolz, Daiana (Frontiers in Medicine, 2021)
Common to several allergic diseases is the generation of immunoglobulin E (IgE) by plasma cells, when exposed to an innocuous antigen. Asthma and chronic obstructive pulmonary disease (COPD) are two prevalent chronic airway inflammatory diseases. Asthma is mediated in some patients through eosinophilic inflammatory mechanisms that include allergic sensitization and Th2-mediated immune airway response. COPD, on the other hand is mainly considered a Th1-mediated inflammatory process with neutrophilic predominance or a non-Th2 inflammation, occasionally associated with the presence of airway bacteria or viruses. IgE production appears to play an important role in the development of both COPD and asthma, as it has been associated to respiratory symptoms, lung function, bacterial and viral infections, airway remodeling and bronchial hyperreactivity in both diseases. The aim of this review is to summarize all current data concerning the role of specific and total IgE in COPD and asthma and to highlight similarities and differences in view of possible therapeutic interventions (Figure 1).